OPTIMIZATION OF INTENSIVE CARE IN CRITICAL CONDITIONS IN PATIENTS WITH PERIPARTUM CARDIOMYOPATHY - Obloberdiyev Muhammad; Joniev S.Sh. (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract Peripartum cardiomyopathy (PPCM) is a rare but potentially fatal complication of pregnancy. The article analyzes modern strategies of intensive care in critical forms of PPCM. Pharmacological and non-pharmacological methods are described, including the use of bromocriptine, inotropes, and mechanical circulatory support devices (IABP, ECMO). Data from clinical studies and an algorithm for managing patients in the ICU are presented. The importance of a multidisciplinary approach is emphasized.